2019
DOI: 10.3390/molecules24091692
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antioxidant and Analgesic Activities of Incarvillea compacta Maxim from the Tibetan Plateau

Abstract: Incarvillea compacta Maxim is a traditional Tibetan plant widely used to treat rheumatic pain and bruises. We conducted qualitative analyses by liquid chromatography-mass spectrometry and quantitative analyses of the total phenols, flavonoids, and alkaloids content of different extracts of I. compacta Maxim. Antioxidant and analgesic activity were analyzed. The results showed that the methanol extract had the highest content of the various ingredients. A total of 25 constituents were identified, of which compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…A recent study [27] showed that the FRAP and DPPH radical-scavenging activity of the ethanol extract of Melissa officinalis L. leaves were lower than ascorbic acid (control), which were consistent with our present findings. However, the current study has confirmed that the in vitro antioxidant activities of HFF are stronger than Impatiens balsamina L. [18], Agastache rugosa (Korean mint) [28], and Incarvillea compacta Maxim [29]. It is generally proven that the antioxidant activity of plants depends on the amounts of biologically active compounds (flavonoids, phenolics, phenylpropanoids, etc.).…”
Section: In Vitro Antioxidant Activities Of Hff Extractssupporting
confidence: 67%
“…A recent study [27] showed that the FRAP and DPPH radical-scavenging activity of the ethanol extract of Melissa officinalis L. leaves were lower than ascorbic acid (control), which were consistent with our present findings. However, the current study has confirmed that the in vitro antioxidant activities of HFF are stronger than Impatiens balsamina L. [18], Agastache rugosa (Korean mint) [28], and Incarvillea compacta Maxim [29]. It is generally proven that the antioxidant activity of plants depends on the amounts of biologically active compounds (flavonoids, phenolics, phenylpropanoids, etc.).…”
Section: In Vitro Antioxidant Activities Of Hff Extractssupporting
confidence: 67%
“…Past research described the V. amygdalina was one of the potential therapeutic to analyse toxicity test [50]. The Carrageenan provoked rat was a better model to estimate the anti-oedematous effects of herbal yield with biphasic in nature [51]. The primary phase involving in the discharge of serotonin and the expressing of histamine in the second phase (after 1 h) was mediated by prostaglandins, cyclooxygenase harvest and the stability lying between two phases was offered by kinins [52].…”
Section: Discussionmentioning
confidence: 99%
“…(1) 1,1-Diphenyl-2-picrylhydrazyl (DPPH) Assay . The scavenging ability of the DPPH free radicals of the three extracts was determined using the reported methods [ 11 , 12 ]. DPPH (0.09 mM of methanol) (0.8 mL) was added to the extraction solution of different concentrations (0.2 mL).…”
Section: Methodsmentioning
confidence: 99%